Vanadium and zinc isotope ratios in lunar basalts - Hopkins, S (2019)
Measurements of isotopic ratios have been useful in understanding the formation and evolution of planetary bodies in our Solar System. However, studies have typically been limited in sample overlap, thereby limiting possible interpretation. This study presents the first highprecision vanadium isotope data, zinc isotope data (via double-spiking), and trace-element data for a suite of lunar basalts. Companion analyses of chlorine and sulphur isotope ratios were obtained at University of New Mexico and University of Maryland.